Prescription of antibiotics in after-hours clinics - Palma, Raquel Mateus (2002)
Aim: To assess antibiotic prescribing in an out-of-hours attendance service. Design of study: Cross-sectional, descriptive, observational survey. Setting: A primary health care facility (Vialonga Health Unit, Póvoa de Stª Iria Health Centre). Methods: A random sample of medical episode records of out-of-hours attendance service from the year 2000 was performed. 1722 records were studied. Variables studied were the patients gender, age, antibiotic prescribing, drug used and pharmacotherapeutic group, diagnosis and doctor prescribing. Results and conclusions: There was registration of antibiotic prescription in 399 (23.3%) of the episode records. Macrolides accounted for the group more frequently prescribed (30% of prescriptions) and benzylpenicillins were chosen in 2,2 % of cases. Acute tonsillitis accounted for the majority of antibiotic prescriptions. Taking into account the growing resistance of group A streptococci to macrolides, these results deserve attention. Third generation cephalosporins and quinolones were widely used, in 10.2% and 7.7% of cases respectively. In 19 cases of acute otitis media (29,7%) third generation cephalosporins, not recommended by available evidence, were used. Quinolones were the drugs of choice in 67% of cystitis cases, and cotrimoxazole, the drug of first choice for uncomplicated cystitis according to current recommendations, was used in 7.5%. The acknowledgement and compliance with current guidelines for antibiotic use is an urgent task.